Belize : Statistical Appendix. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2000)
In this paper, the following statistical data are presented in detail: selected economic indicators, indices of industrial products, central government revenues and expenditure, interest rates, commercial bank's liquidity positions, balance of payments, summary accounts of financial sector, main agricultural products, operations of central government, sugar exports by market, price structure of petroleum products, treasury bills by holder, principal domestic exports, direction of trade, terms of trade, external debt by creditor and borrowing agents, consumer price index, visitor arrivals, and so on.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet